(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The two nations with the greatest populations worldwide are China and India, whose economiesare also expanding at the quickest rates. The greatest pools of highly trained laborers in the world arefound in these two Asian tigers together, and it is widely believed that these two nations will continue todrive global economic development in the twenty-first century. There is a significant possibility foradditional expansion as seen by the recent fast rise in bilateral commerce between the two nations. China,known as the factory of the world, has been expanding at an astounding rate of 10 a year, while India,known as the back office of the world, is expanding at a rate of about 7. However, what makes thetwo giants particularly potent is how their strengths complement one another. In this paper, researchersstudy China’s and India’s roles in global trade.